2021
DOI: 10.1108/fs-07-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous conformable systems for imperceptible computing

Abstract: Purpose Although conformable devices are commonly designed to couple with the human body for personalized and localized medicine, their applications are expanding rapidly. This paper aims to delineate this expansion and predict greater implications in diverse fields. Design/methodology/approach Today’s device technologies continue to face fundamental obstacles preventing their seamless integration with target objects to effectively access, evaluate and alter self-specific physical patterns, while still provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Flexible sensors are expected to revolutionize many fields because of the capability of continuously and wirelessly reporting the physicochemical status of irregularly shaped and dynamically deforming objects. A survey of research over the past decade has revealed the potential use of flexible sensors in many fields beyond healthcare, such as interactive teaching and surgical modeling, expression and creation (music, visual arts, textiles, and fashion), robotics, prosthetics, brain-computer interfaces, urban planning, buildings and infrastructure, agriculture and veterinary care, climate, renewable energy, and ocean and space exploration . Which of these potential applications demonstrated in labs are worth the translational effort remains a tough yet critical question.…”
Section: Lab To End-usermentioning
confidence: 99%
“…Flexible sensors are expected to revolutionize many fields because of the capability of continuously and wirelessly reporting the physicochemical status of irregularly shaped and dynamically deforming objects. A survey of research over the past decade has revealed the potential use of flexible sensors in many fields beyond healthcare, such as interactive teaching and surgical modeling, expression and creation (music, visual arts, textiles, and fashion), robotics, prosthetics, brain-computer interfaces, urban planning, buildings and infrastructure, agriculture and veterinary care, climate, renewable energy, and ocean and space exploration . Which of these potential applications demonstrated in labs are worth the translational effort remains a tough yet critical question.…”
Section: Lab To End-usermentioning
confidence: 99%
“…In this study, we report a hands-free IFS system, the conformable ultrasound patch (cUSP), with small (0.8 cm 2 ) piezoelectric discs (PZT-Ds) optimally positioned within a conformable poly(dimethylsiloxane) (PDMS) substrate. [49][50][51] Leveraging a conformal platform allows tight control of the relative spacing between the ultrasound source and the curvy target membrane. The resulting cavity provides a 1 mm-deep reservoir space for the coupling fluid medium wherein inertial cavitation, convective mixing, and microjet formation can be induced on the surface of the skin.…”
Section: Qualitative Assessment Onlymentioning
confidence: 99%
“…This good reliability is attributed to the low aspect ratio of the pillar (0.7) in the adhesion layer, which makes it less likely to collapse during the attaching and detaching cycles 33 . The adhesion requires an improved understanding of the factors related to face mask non-compliance, gathered in the form of feedback and data from users under real-world scenarios, as well as proactive conformable decoding of this information 19,20 . Considering the difficulty in self-assessing the fit quality and the prevalence of counterfeits, providing real-time fit quality feedback directly to users is also of great value 9 .…”
Section: Mechanical Characterization Of the Components In Cmaskmentioning
confidence: 99%
“…Embedded wearable electronics could potentially be used to achieve a conformable interface with skin, decode biological signals and record the status of the face mask 4,[20][21][22] . However, current wearable electronic devices-which include patches 23 , smartwatches 24,25 and face-mask-compatible systems 26,27 -are only intended to monitor biological signals and symptoms related to infectious diseases [25][26][27] , including breathing patterns 26,[28][29][30] , infection with COVID-19 (ref.…”
Section: Mechanical Characterization Of the Components In Cmaskmentioning
confidence: 99%